THE PRECAUTIONARY PRINCIPLE AND PREVENTIVE CONTROL OF ENVIRONMENTAL DAMAGE BY PUBLIC ADMINISTRATION - Morganti Martins Silva, Daniela; de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2026)
This article examines the precautionary principle as the legal foundation for preventive administrative action in environmental damage control within the Brazilian environmental law framework. It is grounded on the premise that environmental protection, as a fundamental right of a diffuse and intergenerational nature, requires normative instruments capable of anticipating and managing environmental risks, particularly in contexts marked by scientific uncertainty. The study analyzes the legal regime governing environmental protection, emphasizing the central role of principles as interpretative vectors within the legal system. It further explores the formation, normative content, and function of the precautionary principle in contemporary environmental law. The research adopts a doctrinal and jurisprudential approach, demonstrating that the precautionary principle operates as a binding legal directive guiding public authorities toward preventive, mitigating, and risk-control measures. Ultimately, it highlights the relevance of precaution as a structural element for effective environmental governance and sustainable development.